The Effects of Mediating Job Satisfaction on Organizational Citizenship Behaviors with Servant Leadership and Human Relations as Antecedent Variables - Ramdani Bayu Putra; Hasmaynelis Fitri (AMAR (Andalas Management Review), 2021)
This study aims to analyze the Mediating Effects of Job Satisfaction on Organizational Citizenship Behaviors with Servan Leadership and Human Relations as Antecedent Variables in PT. Andalan Mitra Prestasi in the City of Padang. The population and sample of this study were 60 respondents with the sampling technique using the total sampling method. The method used is Structure Equation Modeling (SEM) with the help of the SmartPLS 3 program. The results showed that servant leadership and human relations factors have a significant positive effect in determining the level of job satisfaction and Organizational Citizenship Behaviors. Furthermore, it was also found that job satisfaction also determines or can motivate employees to have Organizational Citizenship Behaviors at work. This study also found that job satisfaction as a mediating or intervening variable can strengthen the influence of servant leadership and human relations in improving Organizational Citizenship Behaviors. The research results can be an input for organizations. In improving Organizational Citizenship Behaviors, management needs to strengthen and pay attention to the Servan leadership and Human relations factors accompanied by paying attention to increasing job satisfaction. So that the level of Organizational Citizenship Behaviors that is expected to be maximized can be realized.